Sedentary behaviour, physical activity, and sarcopenia among older adults in the TSHA: isotemporal substitution model. Issue 1 (28th March 2019) - Sánchez‐Sánchez, Juan Luis; Mañas, Asier; García‐García, Francisco José; Ara, Ignacio; Carnicero, Jose Antonio; Walter, Stefan; Rodríguez‐Mañas, Leocadio
Abstract: Background: The associations between free‐living physical activity (PA) and sedentary behaviour (SB) and sarcopenia in older people and its determinants are controversial. Self‐reporting, the use of one‐size‐fits‐all cut‐points for intensity categorization when using accelerometers and the absence of a clear sarcopenia definition hampered explorations. The aim of this study is to describe the associations between objectively measured PA patterns and sarcopenia and its determinants. Methods: Subjects aged >65 with valid accelerometry and sarcopenia‐related measures from Toledo Study of Healthy Aging (TSHA) were included. Muscle mass (MM) was estimated by dual‐energy X‐ray absorptiometry. Handgrip strength (HS) was measured by dynamometry. Physical performance assessment relied on gait speed (GS). Sarcopenia presence was ascertained using Foundation for the National Institutes of Health (FNIH) criteria. PA and SB were estimated by ActiTrainer worn for 1 week and classified into time spent in SB and different PA intensity bands [light PA (LPA) and moderate‐to‐vigorous PA (MVPA)] using age‐specific cut‐points. Different multivariate linear and logistic regression models [(i) single‐parameter, (ii) partition, and (iii) isotemporal substitution models] were used for estimating associations between PA, SB, and sarcopenia determinants and sarcopenia rates, respectively. All models adjusted for age, sex, co‐morbidities (Charlson index), and functional ability (Katz and Lawton indexes). Results: Five hundred twelve subjects from the TSHA had available data (78.08 ± 5.71 years of age; 54.3% women). FNIH sarcopenia assessment was performed in 497 subjects (23.3% were sarcopenic). In the linear regression, the single‐parameter model showed an association between MVPA and all sarcopenia determinants. In the partition model, MVPA was associated with greater MM and GS. The isotemporal substitution showed that reallocating 1 h/day of MVPA displacing SB was associated with greater values in MM [ β  = 0.014; 95% confidence interval (CI) = 0.004, 0.024; P  < 0.01], GS ( β  = 0.082; 95% CI = 0.054, 0.110; P  < 0.001), and HS ( β  = 0.888; 95% CI = 0.145, 1.631; P  < 0.05). In the logistic regression, the single‐parameter model yielded a significant association between 1 h/day increase in MVPA and sarcopenia reduction [odds ratio (OR) = 0.522; 95% CI = 0.367, 0.726; P  < 0.001], as did the partition model (OR = 0.555; 95% CI = 0.376, 0.799; P  < 0.01). The reallocation of 1 h/day SB only yielded a significant lower sarcopenia risk by almost 50% when it was substituted with MVPA, whereas the substitution of 15 min/day yielded a significant lower sarcopenia risk by 15% ( P  < 0.001) but did not show any association when it was substituted with LPA. Conclusions: An increase in MVPA replacing SB and LPA was associated with a reduction in sarcopenia prevalence and better performance across its determinants (MM, GS, and HS). LPA did not show any significant effect.